Characterization of the limited specificity of antigen recognition in earthworms - Bilej, M; Tucková, L; Romanovský, A (Folia microbiologica, 1995)
Earthworms respond to parenteral stimulation with a protein antigen by the formation of an antigen-binding protein. Earthworms were parenterally stimulated with different proteins and the protein binding was estimated in vitro on both humoral and cellular levels. The binding was significantly higher when the same protein was used for in vivo stimulation. The degree of specificity of the antigen-binding protein after the secondary in vivo challenge increased, but even so it was considerably lower than that of vertebrate immunoglobulins.
Keywords: Arsanilic Acid; imunizace; sérový albumin; Oligochaeta; Epitopes; kyselina arsanilová; hapteny; proteiny; Adjuvants, Immunologic; Proteins; Serum Albumin; Animals; epitopy; Immunization; Haptens; adjuvancia imunologická; zvířata